Regeneration development of salford quays: the benefits to its residential development growth / Faza Fayza Mohd Fawzy, Siti Rahayu Zakaria and Nur Lesya Firsya Johaimi Ling - Mohd Fawzy, Faza Fayza; Zakaria, Siti Rahayu; Nur Lesya Firsya, Johaimi Ling (2012)
Cities and town has always been the centers for any economic growth. However over time they age, evolve and change. In time those cities are either abandoned from its prior use, deteriorated in time or even had undergone unexpected disastrous event such as hurricane or flood. This study aimed to discover alternative ways to transform an ageing and deprived areas to a vibrant and sustainable environment by implementing urban regeneration. Therefore this research taken an interest in studying how the procedure of regeneration development in Salford quays have benefit the elevation of the place from its infamous past. In order to obtain information on Salford Quays and from it construct deliberate analysis and conclusions, this research used statistical data based upon Salford Quays such as its Employment Rate, Income Rate, Housing Demands and Supply, Economy Activity, Crime Rate and Deprivation level in Salford. As a conclusion, the statistical data portrays encouraging results of success on Salford Quays by proving that regeneration development has the potential to reconstruct the development of abandoned areas such as the once neglected dock of Salford Quays which did not catch the eye of investors.